Vigilantisme dan Antinomi Keadilan: Tinjauan Filosofis Plato dan Aristoteles - Paramesti, Nirwasita Zada; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze two main issues: the antinomy of justice between substantive justice, rooted in Plato’s moral idealism, and procedural justice, rooted in Aristotle’s rationality, as well as how vigilantism emerges as a consequence of this tension. The research employs a normative legal method with philosophical, conceptual, and case study approaches. Data are analyzed qualitatively and deductively through comprehensive library research to draw interpretative conclusions. The findings reveal that the antinomy of justice stems from the fundamental differences between Plato’s moral idealism, which focuses on substance and conscience, and Aristotle’s rational realism, which emphasizes procedure or the order of positive law. It is found that vigilantism is not merely a criminal act but rather a philosophical challenge posed by society against the state. This phenomenon erupts when the public experiences a crisis of trust and perceives the system of positive law as rigid, slow, and morally bankrupt formalism. The anger of the masses represents an effort to reclaim substantive justice by consciously disregarding procedures deemed to have failed.